Coalition politics among opposition parties in Malaysia - Hairi, Nur Atika; Bakashmar, Muhammad Rashaad (IIUM Press, International Islamic University Malaysia, 2017)
The study is primarily based upon the party manifestos, documents and collection of results of the 2008 and 2013 General Election in Malaysia Election Commission. The political parties, their constituencies, seats won, seat lost and to whom and where, were analysed. Issues pertaining to the general elections and afflicting problems of the Pakatan Rakyat are also examined. The purpose of this study is to analyse the performance of PR coalition parties (PKR, PAS and DAP) from 2008 to 2015 by examining the background, the results of the elections and issues that affected the performance of the PR coalition parties. There were many issues and challenges whether internal or external that influenced the stability of the PR, especially the loss of the main leaders in PR, fundamental ideological differences, crisi relationship among PR component parties, no longer issues, personalities and power, distribution of seats, manifestos, campaigns, political attacks from incumbent party and the fear of the people. the strenghs and weaknesses of PR will be measured based on the selected contemporary issues in order to show how the Pakatan Rakyat have dealt with various political challenges that it faced. finally, the reasons dissolution of PR will be analysed.